Pengaruh Intensitas Aset Tetap, Intensitas Persediaan dan Kompensasi Manajemen terhadap Manajemen Pajak - Cindy, Cicilia; Kezia Josephine (Lembaga Teewan Journal Solutions, 2026)
Tax management refers to a company’s efforts to manage its tax obligations by controlling, planning, and organizing all taxation-related activities in order to ensure that they are carried out effectively, efficiently, and in accordance with applicable tax regulations. This study aims to examine the factors influencing tax management, particularly fixed asset intensity, inventory intensity, and management compensation in primary consumer goods sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Tax management is measured using the effective tax rate, calculated as income tax expense divided by profit before tax. This study employs secondary data in the form of financial statements and/or annual reports obtained from the official website of the Indonesia Stock Exchange. The sampling technique used in this study is purposive sampling, resulting in 54 companies selected based on predetermined criteria and . The data were processed using EViews version 14, and the analytical method applied in this research was panel data regression analysis. This study proposed three hypotheses; however, only one hypothesis was accepted. The findings indicate that inventory intensity has a significant effect on tax management. In contrast, fixed asset intensity and management compensation do not have a significant effect on tax management. After the outliers became 34 companies.